Health insurance service model on the basis of patient-centered care: a scoping review - Imron, Moh Ali; Astuti, Andari Wuri; Faidullah, Hilmi Zadah; Wantonoro; Fatimah, Siti; Manurung, Khaterina Kristina; Febriyanti, Maya; Siregar, Dedy Revelino; Baros, Wan Aisyah (Universitas Aisyiyah Yogyakarta, 2024)
Health insurance provides access to every color of the country to get access to health services in the form of promotive, preventive, curative, and rehabilitative efforts at affordable costs. Integrated health services that focus on patient needs (patient-centered care) will increase the active role of families and communities in making decisions related to health services to be provided and are often associated with health financing and insurance used. This Scoping review aims to explore and map the scientific evidence related to the health insurance model in patient-centered care-based health services. This study uses Arkshey & O'Malley Framework and PRISMA-ScR Checklist. In the identification of articles used using PubMed, EBSCO, ProQuest, Wiley Online Library, and Grey supporting literature such as Google Scholar and appropriate databases. The article inclusion criteria used in the search are primary articles in 2012-2022, articles from relevant Gray literature and databases, scientific articles in English and/ or Indonesian, and scientific articles that focus on the health care insurance model and patient-centered care-based health services. While the exclusion criteria used are articles in the form of guidelines, standard operating procedures, opinion papers, reviews, commentaries, research articles that do not use English and Indonesian, and research articles that focus on medicine-centered care are not included in this review. The keywords used are patient-centered care and health insurance. Assessment of Article quality using the Critical Appraisal Skills Program (CASP) and Joanna Bridge Institute Tools (JBI). A total of 6,388 articles were selected and 14 articles were reviewed. Research articles were reviewed from 8 countries with 12 articles using quantitative research design and 2 articles using qualitative research design. From the review article, the author identified 2 main themes, namely the use of health insurance and the application of patient-centered care. Patient satisfaction among Health Insurance users is higher than patients who do not use health insurance because health insurance provides financial protection for health services. The use of health insurance based on patient-centered care is expected to provide positive benefits to health services such as improving patient healing, reducing unnecessary actions/ care, and reducing the length of hospital treatment so that it is expected to reduce the financing made by patients and health insurance used.